Assessing viscoelastic properties of concrete during its early ages through forced dynamic excitation of test beams - Granja, José Luís Duarte (2016)
This paper aims to demonstrate the feasibility of a recently proposed approach (termed VisCoDyn) to assess the viscoelastic behaviour of concrete from the earliest ages, by introducing a known dynamic excitation to a simply supported specimen. The method involves the continuous monitoring of the response of the tested sample in terms of amplitude (force and displacement), as well as the evaluation of the phase lag between the applied force and the response. The acquired data is then used to calculate the storage and loss moduli, according to procedures that are normally used in the context of material testing in polymer science. Indeed, the loss modulus is known to be relatable to the viscoelastic properties of materials. The paper presents the current state of development of the VisCoDyn test methodology together with several test results obtain in specimens that were tested during the first 24 hours of curing. Parallel testing with other techniques is also presented for reference